Quantification of vector and host competence for Japanese Encephalitis Virus: a systematic review and meta-analyses of the literature - da Silva Oliveira, Ana Rute (Kansas State University, 2017)
Japanese encephalitis virus (JEV) is a virus of the Flavivirus genus that may result in encephalitis in vertebrate hosts. This vector-borne zoonosis occurs in Eastern and Southeastern Asia and an intentional or inadvertent introduction into the United States (US) would lead to important public health and economic consequences. The objective of this study was to gather, appraise, and synthesize primary research literature to identify and quantify vector and host competence for JEV, using a systematic review-metaanalysis (SR-MA) approach. After defining the research question, we performed a search in selected electronic databases. The title and abstract of the identified articles were screened for relevance using a defined set of exclusion and inclusion criteria, and relevant articles were subjected to a risk of bias assessment followed by data extraction. Random-effects subgroup meta-analysis models were fitted by species (mosquito or vertebrate host species) to estimate pooled summary measures as well as to compute the variance between studies. Meta-regression models were fitted to assess the association between different predictors and the outcomes of interest and to identify sources of heterogeneity among studies. Data were extracted from 171 peer-reviewed articles. Most studies were observational (59.06%) and reported vector competence (60.2%). The outcome measures reported pertained to transmission efficiency, host preference, and vector susceptibility to infection within vector competence; and susceptibility to infection within host competence. All outcome measures (JEV proportion of infection in vectors and hosts from observational studies; and JEV infection, dissemination, and transmission rates in vectors from experimental studies) had high heterogeneity. Mosquito species, diagnostic method, country, and capture method represented important sources of heterogeneity associated with the proportion of JEV infection in vectors; host species and region were considered sources of heterogeneity associated with the proportion of JEV infection in hosts; and diagnostic and mosquito capture methods were deemed important contributors of heterogeneity for the minimum infection rate (MIR) outcome. Mosquito species and administration route represented the main sources of heterogeneity associated with JEV infection rate in vectors. Quantitative estimates resulting from this SR-MA will be inputted into risk assessment models to evaluate risks associated with the introduction of JEV in the US.
Keywords: Japanese encephalitis; Japanese encephalitis virus; Systematic review; Meta-analysis; Vector competence; Host competence